2005
DOI: 10.1128/aem.71.5.2365-2371.2005
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Plant Hormone Indole-3-Acetic Acid for Growth by Pseudomonas putida Strain 1290

Abstract: We have isolated from plant surfaces several bacteria with the ability to catabolize indole-3-acetic acid (IAA). One of them, isolate 1290, was able to utilize IAA as a sole source of carbon, nitrogen, and energy. The strain was identified by its 16S rRNA sequence as Pseudomonas putida. Activity of the enzyme catechol 1,2-dioxygenase was induced during growth on IAA, suggesting that catechol is an intermediate of the IAA catabolic pathway. This was in agreement with the observation that the oxygen uptake by IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
155
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(179 citation statements)
references
References 44 publications
9
155
0
15
Order By: Relevance
“…There are several examples of plant-associated bacteria capable of degrading auxins. 33,52,53 The capacity of G. xylinus to utilize auxins as carbon source will be explored in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples of plant-associated bacteria capable of degrading auxins. 33,52,53 The capacity of G. xylinus to utilize auxins as carbon source will be explored in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been suggested that IAA could also be a native signalling molecule in bacteria (Spaepen et al, 2007). The fact that several bacteria can catabolize IAA and use it as a sole source of carbon, nitrogen and energy (Leveau and Lindow, 2005), more information is needed about its possible role as signalling agent in bacteria. The GAs were first identified from the fungus Gibberella fujikuroi and are now known to occur in several species of bacteria, fungi, ferns and seed plants (reviewed by Johri, 2004).…”
Section: Occurrence Of Phytohormones In Bacteria and Fungimentioning
confidence: 99%
“…1972;Mohn et al, 1999). The Z. resiniphila genomes harbor multiple monooxygenase, dioxygenase and dehydrogenase genes for aerobic degradation of aromatic compounds including toluene, benzoate, 2-nitrobenzoate, long-chain alkylphenol (lap), cinnamic acid, pcymene, indole-3-acetic acid, cyclohexanecaboxylate, extradiol, and xanthine (Muraki et al, 2003;Leveau and Lindow, 2005;Kung et al, 2014). The catechol derivatives could be oxidized by central meta-cleavage pathway to 2-hydroxymuconic semialdehyde by catechol 2,3-dioxygenase in the Zoogloea strains (Arai et al, 2000).…”
Section: Carbon Source Utilizationmentioning
confidence: 99%